Pseudomonas xionganensis sp. nov., isolated from Baiyangdian Lake in Xiong'an New Area. Issue 12 (30th December 2020) - Zhao, Yingying; Yang, Yunzhen; He, Fei; Wang, Chao; Feng, Jie; Zhang, Xiumin
Abstract : An aerobic, Gram-stain-negative, rod-shaped bacterium, designated as strain R-22–3 w-18 T, was isolated from Baiyangdian Lake in Xiong'an New Area, PR China. Growth was observed at 15–37 °C (optimum, 30 °C) and pH 7.0–10.0 (optimum, pH 8.0). 16S rRNA gene sequence analysis placed the strain in a separate branch in the Pseudomonas putida group, with Pseudomonas anguilliseptica DSM12111 T as its closest phylogenetic relative (98.2 %). Whole-genome comparisons, using average nucleotide identity (ANI), average amino acid identity (AAI) and digital DNA–DNA hybridization (dDDH) analyses, confirmed low genome relatedness to the closely related Pseudomonas species [below the recommended thresholds of 95 % (ANI), 95 % (AAI) and 70 % (DDH) for species delineation]. Phenotypic characterization tests could also distinguish this strain from other related species of the genus Pseudomonas . Therefore, based on genetic and phenotypic evidence, it is clear that strain R-22–3 w-18 T represents a novel species of the genus Pseudomonas, for which the name Pseudomonas xionganensis sp. nov. is proposed. The type strain is R-22–3 w-18 T (=CGMCC 1.17250 T =KCTC 72658 T ).